Demographic Diversity and Change in the Central American Isthmus - Centro Centroamericano de Población (CCP) (1997)
The chapters in this volume were originally presented at the International Conference on the Population of the Central American Isthmus, organized by the Central American Population Program (PCP) at the University of Costa Rica in collaboration with colleagues at RAND. Both the papers at the conference and the subset that are included in this volume represent research in a broad range of disciplines including demography, public health, anthropology, history, sociology, human ecology, and economics. The conference played an important role in bringing together an international group of researchers working on related issues in the region. The objective of this volume is to provide, in one central location, a collection of recent research on demographic, social, and environmental issues in the Central American Isthmus for English-speaking readers, both those who are not familiar with the region and those who know it well. For Spanish-speakers, the same collection of papers has been independently published as De los Mayas a la planificación familiar: DemografÍa del Istmo (L. Rosero Bixby, A. Pebley, and A. Bermúdez Méndez, editors) by the Editorial de la Universidad de Costa Rica.